Parotid Gland Metastases of Cutaneous Squamous Cell Carcinoma of the Head: Occult Metastases Occurrence and Their Late Manifestation - Horakova, Zuzana; Starek, Ivo; Zapletalova, Jana; Salzman, Richard (International journal of clinical practice, 2024)
Cutaneous squamous cell carcinomas (cSCC) are malignant tumours with excellent prognosis unless nodal metastases develop. The aim of our study is to determine the prognostic significance of the clinical stage of parotid gland metastases and the incidence of occult cervical lymph node involvement in cSCC of the head. Our retrospective analysis includes 39 patients with cSCC parotid gland metastases, 15 of whom had concurrent cervical node involvement. In 32 patients, the lymph nodes manifested at stage N3b. A total of 26 patients were treated with parotidectomy, 9 patients received radiotherapy alone, and 4 received symptomatic therapy. The surgical treatment included either total conservative (21 cases) or superficial parotidectomy (5 cases) and neck dissection (therapeutic neck dissections in 11 cases and elective in 14 cases). In all cases, surgery was performed with sufficient tumour-free resection margins. Adjuvant radiotherapy was administered postoperatively in 16 patients. Occult metastases were present in 21% of cases after an elective neck dissection, but not in any case in the deep lobe of the parotid gland. The five-year overall survival and recurrence-free interval were 52% and 55%, respectively. Patients with the cN3b stage and G3 histological grade tend to have a worse prognosis, but not at a statistically significant level. The prognosis was not worse in patients with concurrent parotid and cervical metastases compared to those with metastases limited to the parotid gland only. The addition of adjuvant irradiation, in comparison to a single modality surgical treatment, was the only statistically significant prognostic factor that reduced the risk of death from this diagnosis (p=0.013). The extent of parotidectomy (partial vs. total) had no impact on either the risk of recurrence or patient prognosis. The combination of surgery with irradiation provides the best results and should be applied to all patients who tolerate the treatment. A partial superficial parotidectomy should be sufficient, with a minimum risk of occult metastasis in the deep lobe. Conversely, the relatively high incidence of occult neck metastases indicates that patients could likely benefit from elective neck dissection.
Keywords: Parotid Gland; Neoplasm Staging; staging nádorů; Parotid Neoplasms; spinocelulární karcinom; retrospektivní studie; Humans; Carcinoma, Squamous Cell; nádory kůže; Retrospective Studies; Skin Neoplasms; lidé; parotis; nádory příušní žlázy